Amplifying toughness in silica-reinforced natural rubber by preserving long chains - Matthew Wei Ming Tan; Guodong Nian; Zheqi Chen; Xianyang Bao; Yakov Kutsovsky; Zhigang Suo (Proceedings of the National Academy of Sciences, 2026)
Natural rubber outperforms synthetic rubbers because of its long chains and strain-induced crystallization (SIC). However, these advantages are largely lost when the natural rubber chains are masticated during processing, and silica particles are added for reinforcement. Mastication eases mixing but shortens chains and lowers performance. Silica particles require covalent interlinks with rubber chains, but these interlinks restrict chain stretch and alignment, reducing SIC. Here, we show that the performance of silica-reinforced natural rubber can be markedly enhanced by preserving long natural rubber chains. We use a solvent to dissolve natural rubber latex into individual rubber chains and use the solution to uniformly disperse silica particles. After drying, the uncured compound can be stored and molded prior to curing. The long rubber chains are then sparsely crosslinked with one another and interlinked with the silica particles. The long strands readily align under stretch and increase SIC. Preserving long chains elevates toughness by an order of magnitude, from ~2 to 44 kJ m –2 . High toughness arises from energy dissipation across multiple length scales, over long rubber strands, silica particles, and a zone of SIC. High modulus of ~19 MPa arises from two interpenetrating networks: the network of densely entangled rubber chains and the network of percolated silica particles. The resulting material achieves high toughness while maintaining high modulus, a combination uncommon in silica-reinforced synthetic and natural rubbers.